Uganda : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory Note discusses key priorities for strengthening Uganda's Poverty Eradication Action Plan (PEAP) and for ensuring its effective implementation. PEAP 2004 describes the participatory process underpinning the development of the PEAP strategy, provides a poverty diagnosis, and presents policy measures, sector plans, costing, and a result-oriented policy matrix for sustainable economic growth and poverty reduction over the 2004/05-2007/08 period. It argues for a shift of the policy focus from recovery to sustainable growth and structural transformation, and presents specific government policies to accelerate poverty reduction.